Today and tomorrow : emerging practices in Malaysian art - Ooi, Adeline; Yong, Beverly; Ng, Rachel (Kuala Lumpur : Adaptus Design System Sdn Bhd, 2013)
This book provides a snapshot of 27 artists representing the diversity and energy of today's art scene in Malaysia.
Keywords: Artists -- Malaysia; Art, Malaysian -- 21st century; Art, Modern -- 21st century -- Malaysia